Regional and epidemiological characteristics of tuberculosis and treatment outcomes in West China - Wang, Qiaolan; Zhu, Jiangchuan; Zhang, Luoning; Xie, Linshen (Frontiers in Public Health, 2023)
Objective To understand the prevalence and treatment outcome of tuberculosis in a typically regional County from 2016 to 2021, so as to provide reference and basis for the prevention and treatment of tuberculosis in this area. Methods Descriptive epidemiological methods were used to analyze the population, time and location distribution of pulmonary tuberculosis in Dazhu County from 2016 to 2021. The incidence rates were compared by Chi-square test and trend test, time distribution combined with seasonal index analysis, and the test level was α = 0.05. Results A total of 2,899 cases of pulmonary tuberculosis were reported in Dazhu County from 2016 to 2021, with an average annual incidence rate of 44.29/100,000 and standardized reported incidence rate was 36.77/100,000, showing a downward trend year by year (χ2 trend = 124.629, p < 0.001). A total of 955 cases of pathogen positive were reported, showing an increasing trend year by year (χ2 trend = 59.773, p < 0.001). In terms of time distribution, the incidence rate was high in autumn and winter, and September and December were the peak of the disease in the whole year, and the overall trend increased first, then decreased and once again increased (F = 5.861, p < 0.05). In regional distribution, the highest annual average reported incidence rate was in concentrated population. The incidence rate of male was higher than female in population distribution. After standardization, the overall incidence rate increased from 34 to 45 years old (χ2 trend = 6963.101, p < 0.001), and decreased after 45 years old (χ2 trend = 1104.393, p < 0.001). The occupation distribution is mainly farmers (82.75%). The overall arrival rate and cure rate of patients showed an upward trend year by year (χ2 trend = 4.306, χ2 trend = 5.772, p < 0.001). Conclusion The incidence rate of pulmonary tuberculosis in this regional county is decreasing year by year. Male patients are higher than female patients and have certain seasonal characteristics. Attention should be paid to male, older adult, farmers and other groups, and corresponding measures should be taken to strengthen the prevention and treatment of tuberculosis in high incidence areas.